2021
DOI: 10.3389/fpsyg.2021.612023
|View full text |Cite
|
Sign up to set email alerts
|

From the Basic Psychological Needs Satisfaction to Intrinsic Motivation: Mediating Effect of Academic Integration

Abstract: The studies show a positive and direct relationship between basic psychological needs satisfaction and intrinsic motivation of the students. However, there is a lack of studies that analyze the psychological processes that affect these relationships. For this reason, the purpose of this study was to investigate the mediating role of academic integration on the relationship between basic psychological needs satisfaction and intrinsic motivation of Chilean university students. The participants were a total of 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
2
4
0
1
Order By: Relevance
“…Since internal motivation comes from a learner’s interest in a task, it is necessary to study the influence of personal internal factors on the motivational intensity from the perspective of dynamic development ( Deci and Ryan, 1985 ). In addition, consistent with previous studies, we found that external factors such as monthly household income level and English learning satisfaction can also affect the strength of motivation ( Lee et al, 2009 ; Yu et al, 2018 ; Vergara-Morales and Del Valle, 2021 ). Students’ extrinsic motivation will change with varying stimuli, affecting individuals’ internal motivation ( Van den Broeck et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Since internal motivation comes from a learner’s interest in a task, it is necessary to study the influence of personal internal factors on the motivational intensity from the perspective of dynamic development ( Deci and Ryan, 1985 ). In addition, consistent with previous studies, we found that external factors such as monthly household income level and English learning satisfaction can also affect the strength of motivation ( Lee et al, 2009 ; Yu et al, 2018 ; Vergara-Morales and Del Valle, 2021 ). Students’ extrinsic motivation will change with varying stimuli, affecting individuals’ internal motivation ( Van den Broeck et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, academic motivation was found to be an associated variable in a few types of research (e.g., Levpuscek and Podlesek, 2019 ; Noyens et al, 2019 ). In addition, motivation variables, i.e., autonomous motivation (Miquelon et al, 2005 ; Bailey and Phillips, 2015 ; Willems et al, 2021 ), self-oriented perfectionism (Miquelon et al, 2005 ), self-efficacy, and learning strategies (Willems et al, 2021 ), as well as basic psychological needs satisfaction were also found to be associated with students' academic adjustment (Carr et al, 2013 ; Vergara-Morales and Del Valle, 2021 ). In terms of family factors, parental autonomy support (Daniels et al, 2019 ), parental involvement (Smojver-Ajic et al, 2015 ), and attachment styles were significantly linked to attachment security (positive relationship with the insecurity dimension) (Carr et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pupils' performance hinges on self-efficacy and subject interest (Otunuku and Brown, 2007;Sejčová, 2006), and a positive attitude toward the subject improves educational results (Holúbková and Glasová, 2011). While positive attitude and assigning a high value to subjects induce attention, commitment, and better school performance (Geddes et al, 2010;Ismail, 2009;Schenkel, 2009;Verešová and Malá, 2016), the negative attitude induces fear of the subject and lower results, intensifying negative attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%